2020
DOI: 10.32859/era.20.08.1-19
|View full text |Cite
|
Sign up to set email alerts
|

An overview of Ethnomedicinal plants of Uzbekistan

Abstract: Background: The Flora of Central Asia is extremely rich, with about 9800 species of vascular plants. Uzbekistan, with over 4500 species, has a central position in the region, and is regarded as one of the main centers of medicinal plants diversity, in particular because of its high percentage of local endemism. About 600 species of medicinal plants have been documented in Uzbekistan for the treatment of numerous diseases, many of them endemic. These plants are still used for the medicinal traits in industrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 7 publications
0
24
0
Order By: Relevance
“…These values are well within the range of 32-72 WEPs reported from Jammu and Kashmir (Kumar and Hamal 2009;Dangwal et al 2014;Singh et al 2021), other parts of Indian Himalayas (Aryal et al 2018;Radha et al 2018;, Nepal Himalayas (Bhattarai et al 2009;Uprety et al 2012;Khakurel et al 2021), and the World (Alemnah 2020; Hegazy et al 2020;Purba and Silalahi, 2021;Ahmad et al 2022). However, some studies have reported very high number of WEPs in their studies; 335 WEPs were identified from Hunan, China (Zou et al 2011), 173 WEPs from Xishuanbanna valley, China (Ghorbani et al 2012), 159 WEPs from Heihe valley, China (Kang et al 2012), 111 WEPs from Bandipora, Jammu and Kashmir, India (Singh et al 2016), 90 WEPs from Udhampur, Jammu and Kashmir, India (Bhatia et al 2018), 117 WEPs from Uzbekistan (Khojimatov et al 2020), and 130 plants from Kishtwar region of Jammu and Kashmir, India (Thakur and Dutt 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These values are well within the range of 32-72 WEPs reported from Jammu and Kashmir (Kumar and Hamal 2009;Dangwal et al 2014;Singh et al 2021), other parts of Indian Himalayas (Aryal et al 2018;Radha et al 2018;, Nepal Himalayas (Bhattarai et al 2009;Uprety et al 2012;Khakurel et al 2021), and the World (Alemnah 2020; Hegazy et al 2020;Purba and Silalahi, 2021;Ahmad et al 2022). However, some studies have reported very high number of WEPs in their studies; 335 WEPs were identified from Hunan, China (Zou et al 2011), 173 WEPs from Xishuanbanna valley, China (Ghorbani et al 2012), 159 WEPs from Heihe valley, China (Kang et al 2012), 111 WEPs from Bandipora, Jammu and Kashmir, India (Singh et al 2016), 90 WEPs from Udhampur, Jammu and Kashmir, India (Bhatia et al 2018), 117 WEPs from Uzbekistan (Khojimatov et al 2020), and 130 plants from Kishtwar region of Jammu and Kashmir, India (Thakur and Dutt 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In this invaluable document which is still an authentic reference in a lot of medical schools across the world, about 1500 herbal drugs and almost 800 species of medicinal vascular plants have been discussed in detail. The present form of Unani medicine greatly owes to him (16)(17)(18).…”
Section: Traditional Medicinal System In Iranmentioning
confidence: 99%
“…Several species of this genus have been used in ethno-medicine for the treatment of digestive disorders, headache, dizziness, arthritis, rheumatism, and Fig. 14 The structures of lanostane type triterpenes (66)(67)(68)(69)(70) as proproliferative agents on HFDPCs from the sclerotium of Inonotus obliquus toothache and as tranquilizers in Uzbekistan. The roots of F. varia (Shrenk) Trautv.…”
Section: Phytochemical Studies On Traditional Herbal Medicines Used In Uzbekistanmentioning
confidence: 99%
“…Characteristic herbal medicines only found in Uzbekistan have been used traditionally, since the number of endemic plants in this area is significantly higher than those of the other areas as described above. In addition, seven major ethnic populations with ancestors in Kazakhstan, Turkmenistan, Tajikistan, Afghanistan, Russia, Uzbekistan, and Kyrgyzstan, live in Uzbekistan, and therefore, the wide spectrum of medicinal plant utilizations are found based on ethnic differences [ 67 ]. About 70% of Uzbek households use traditional herbal medicines in their daily lives [ 68 ].…”
Section: Phytochemical Studies On Traditional Herbal Medicines Used In Uzbekistanmentioning
confidence: 99%